(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Citizen participation in local government decision making is increasingly recognized as a crucial element for enhancing democratic governance and improving the quality of public services. This paper investigates the role of citizen involvement in local governance, focusing on its impact on decision making processes, transparency, and accountability. The study aims to understand how local governments incorporate citizen feedback in to policy development and to explore the challenges hindering effective participation. A mixed methods approach is employed, combining qualitative and quantitative data from case studies, surveys, and in depth interviews with local government officials, po licymakers, and citizens. The research analyzes case studies from municipalities with varying levels of citizen engagement, assessing the effectiveness of participatory mechanisms such as public consultations, participatory budgeting, and online platforms. Surveys are conducted to evaluate citizens’ perceptions of participation processes and identify barriers, especially for marginalized groups. Findings indicate that inclusive participatory processes lead to better policy outcomes, as citizens feel more in volved and their concerns are addressed. However, challenges such as low civic education, socio economic disparities, political resistance, and institutional inefficiencies continue to impede the full potential of citizen participation. The paper suggests strategies for overcoming these barriers, such as enhancing civic education, fostering political will, and utilizing digital tools for broader engagement. This study contributes to the discourse on participatory governance by providing actionable recommend ations for improving citizen involvement in local government decision making, with the ultimate aim of strengthening democratic processes and enhancing governance quality.